STRATEGY FOR IMPLEMENTING DIGITAL SKILLS TRAINING AS AN EFFORT TO EMPOWER MSMES IN RURAL AREAS TO INCREASE COMPETITIVENESS AND GLOBAL MARKET ACCESSIBILITY - Charisal Matsen A Manu; Loso Judijanto; Zainal Arifin; Yuarini Wahyu Pertiwi; Nur Aini Bunyani (JOURNAL OF COMMUNITY DEDICATION, 2023)
This research outlines a strategic approach to implementing digital skills training programs to empower Micro, Small, and Medium Enterprises (MSMEs) in rural areas, enhancing their competitiveness and facilitating access to global markets. The strategy encompassed a comprehensive needs assessment to identify specific skill gaps, followed by designing and delivering tailored training modules. Utilizing a blend of online and offline resources, the training initiatives were structured to address diverse sectors within the MSME landscape. Rigorous monitoring and evaluation mechanisms were employed to gauge the effectiveness of the training, allowing for real-time adjustments. The strategy also integrated community engagement to foster a supportive ecosystem, ensuring sustained learning beyond the training sessions. The outcomes demonstrated a notable improvement in digital literacy levels among participants, positively impacting their operational efficiency. The strategic implementation of digital skills training emerged as a catalyst for empowering rural MSMEs, positioning them competitively in the global market.